ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PENGGUNAAN PERSONAL COMPUTER DENGAN TECHNOLOGY ACCEPTANCE MODEL - Handayani, Rini (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2010)
The objectives of the research are to examine some factors that influence personal computer acceptance from user in manufacture company. The study is based on the model proposed by Venkatesh et al.,(2003) and Lin and Wu (2004). This study used data that obtained from individual perception of information sistem user in manufacture company at Surakarta. Data gathered from mail survey.Â Three hundred questionnaires have sent to companies, 105 questionnaires were returned, and only 83 questionnaires can be used. The data were analyzed by using Partial Least Square (PLS) by Smart PLS software. Study results show that social influence give insignificant negative to attitude toward using PC. Perceived ease of use give significant positive to perceived usefullnes and attitude toward using PC. Perceived usefullnes give significant positive to attitude toward using PC. Attitude toward using PC give significant positive to personal computer acceptance. Management support give significant positive to perceived usefullnes and perceived ease of use